Comparison of Communication Algorithms on OTIS-HHC and OTIS-Ring Parallel Architectures (International Journal of Engineering and Computer Science, 2014)
The OTIS (Optical Transpose Interconnection System) has recently attracted the attention of researchers and it has become very popular for solving real life computation and communication intensive applications. In this paper, we have presented a comparison of communication algorithms on OTIS-HHC and OTIS-Ring architectures. Gossiping is a common process for solving some of the problems like polynomial interpolation, matrix multiplication, prefix computation and enumeration sorting. The proposed algorithm is based on some predefined data routing functions. To analyze the time complexity of the proposed communication algorithms, we have considered the data movements on electronic link and optical link. The time complexity of both the proposed algorithms is O(n) OTIS moves and O(n2) electronic moves.